Tingkat Parasitasi Fop/Usarisanus (Hymenoptera: Braconidae) Pada Lalat Buah Belimbing Di Daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
Bactrocera carambolae was found on carambola fruit in Yogyakarta Special Province and there were three species of parasitoids, i.e. F opius arisanus, Agasnaspis sp., and Asobara sp. The populations of Agasnaspis sp. and Asobara sp. were very low and was only found in Samas coastal area. F. arisanus was dominant, and always found in all observation sites. There was no significant result on their parasitism (for region, F(2 35)= 0.057